Proteomic Analysis of Bifidobacterium animalis AR668 and AR668-R1 Under Aerobic Culture - Yaping Liu; Xiaoxiao Zhao; Miao Yang; Xin Song; Guangqiang Wang; Yongjun Xia; Liang Zhao; Zhiqiang Xiong; Lianzhong Ai (Foods)
Bifidobacterium animalis is a widely used probiotic with significant health benefits, but its application is limited by oxygen sensitivity. Our laboratory previously developed an oxygen-tolerant B. animalis AR668-R1 using adaptive laboratory evolution under aerobic culture, but the molecular mechanism remains unclear. In this work, compared to the wild-type parental strain B. animalis AR668, 212 upregulated and 390 downregulated proteins were identified in AR668-R1 under aerobic conditions through comparative proteomic analysis. Enrichment analysis of the differentially expressed proteins between AR668 and AR668-R1 identified the potential oxygen-tolerant related pathways, including the translation process, transmembrane transport system, and carbohydrate metabolism. Furthermore, five potential oxygen-tolerance proteins (DapE, Mth2, MutT, Eno, and MsrAB) were validated by RT-qPCR that may contribute to the aerobic growth of AR668-R1. Through gene overexpression validation, Mth2 (7,8-dihydro-8-oxoguanine triphosphatase) was found to enhance the growth of AR668-R1 by 19.8% compared to the empty plasmid control under aerobic conditions. Our finding provides valuable insights into the oxygen-tolerant mechanisms of B. animalis at the protein level.